L-asparaginase Production by Leucosporidium scottii in a Bench-Scale Bioreactor With Co-production of Lipids - Moguel, Ignacio S.; Yamakawa, Celina K.; Pessoa, Adalberto; Mussatto, Solange I. (Frontiers in Bioengineering and Biotechnology, 2020)
L-asparaginase (ASNase) is a therapeutical enzyme used for treatment of acute lymphoblastic leukemia. ASNase products available in the market are produced by bacteria and usually present allergic response and important toxicity effects to the patients. Production of ASNase by yeasts could be an alternative to overcome these problems since yeasts have better compatibility with the human system. Recently, it was found that Leucosporidium scottii, a psychrotolerant yeast, produces ASNase. In order to advance the production of ASNase by this yeast, the present study aimed to select suitable process conditions able to maximize the production of this enzyme in a bench-scale bioreactor. Additionally, the accumulation of lipids during the enzyme production process was also determined and quantified. Experiments were carried out with the aim of selecting the most appropriate conditions of initial cell concentration (1.0, 3.5, and 5.6 g L-1), carbon source (sucrose and glycerol, individually or in mixture) and oxygen transfer rate (kLa in the range of 1.42 to 123 h-1) to be used on the production of ASNase by this yeast. Results revealed that the enzyme production increased when using an initial cell concentration of 5.6 g L-1, mixture of sucrose and glycerol as carbon source, and kLa of 91.72 h-1. Under these conditions, the enzyme productivity was maximized, reaching 35.11 U L-1 h-1, which is already suitable for the development of scale-up studies. Additionally, accumulation of lipids was observed in all the cultivations, corresponding to 2-7 g L-1 (32 – 40% of the cell dry mass), with oleic acid (C18:1) being the predominant compound (50.15%). Since the L-asparaginase biopharmaceuticals on the market are highly priced, the co-production of lipids as a secondary high-value product during the ASNase production, as observed in the present study, is an interesting finding that opens up perspectives to increase the economic feasibility of the enzyme production process.